PENGARUH STORE ATMOSPHERE TERHADAP KEINGINAN UNTUK BELI KEMBALI DI TAMAN INDIE RESTO KOTA MALANG - Kurniawati, Ratna (Department of Management, 2015)
This study aimed to examine the effect of store atmosphere against the re-purchases intention at Taman Indie Resto and to examine indicators of variable store atmosphere (Exterior, General Interior, Store Layout and Interior Display) the dominant influence on the re-purchases intention at Taman Indie Resto Town Malang. This study uses primary data collected from questionnaires, the purchaser (buyer) at Taman Indie Resto. The sampling technique in this research use accidental sampling, as many as 130 people and using binomial logistic regression analysis. Based on data analysis binomial regression which includes partial test, test simultaneously and the suitability of the model in this study are: test based on partial indicators that affect significantly partially on the re-purchases intention at Taman Indie Resto, with indicators exterior, general interior, store layout and interior display significantly influence the re-purchases intention at Taman Indie Resto. Concurrent test shows that jointly indicators exterior, general interior, store layout and interior displays significantly influence the re-purchases intention at Taman Indie Resto. Indicators of the most dominant influence on the re-purchases intention is the general interior. Test the feasibility of the model shows that the -2 log likelihood with the independent variables indicate that the addition of independent variables in the regression model is better than the absence of independent variables so that the model used is feasible.